Cytotoxic activity against human neuroblastoma and melanoma cells mediated by IgM antibodies derived from peripheral blood of healthy donors - Devarapu, Satish; Mamidi, Srinivas; Plöger, Frank; Dill, Othmar; Blixt, Ola; Kirschfink, Michael; Schwartz‐Albiez, Reinhard (International journal of cancer, 2016)
A small percentage of healthy donors identified in the Western population carry antibodies in their peripheral blood which convey cytotoxic activity against certain human melanoma and neuroblastoma cell lines. We measured the cytotoxic activity of sera and plasmas from healthy donors on the human neuroblastoma cell line Kelly and various melanoma cell lines. Antibodies of IgM isotype, presumably belonging to the class of naturally occurring antibodies, exerted cytotoxic activity in a complement-dependent fashion. Apart from complement-dependent tumor cell lysis, we observed C3 opsonization in all tumor cell lines upon treatment with cytotoxic plasmas. Cell lines tested primarily expressed membrane complement regulatory proteins (mCRP) CD46, CD55 and CD59 to various extents. Blocking of mCRPs by monoclonal antibodies enhanced cell lysis and opsonization, though some melanoma cells remained resistant to complement attack. Epitopes recognized by cytotoxic antibodies were represented by gangliosides such as GD2 and GD3, as evidenced by cellular sialidase pretreatment and enhanced expression of distinct gangliosides. It remains to be clarified why only a small fraction of healthy persons carry these antitumor cytotoxic antibodies.
Gesehen am 07.05.2020